PENGARUH KETERLIBATAN FASHION DAN GAYA HIDUP BERBELANJA TERHADAP PEMBELIAN IMPULSIF (STUDI TERHADAP REMAJA DAN PEMUDA DKI JAKARTA) - Graciella Tansah Gunawan, Tony Sitinjak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
As society becomes more modern in their upbringing, changes in their lifestyle have triggered the development of shopping malls or shopping centers, leading to the increase of impulsive purchases. This study aims to determine the influence of fashion involvement and shopping lifestyle to these impulsive purchases, which occur in the category of fashion products among teenagers and youths in DKI Jakarta with age range 15 to 25 years who work as students, university students, employees, entrepreneurs, and fashion bloggers. This research is using explanation method as the research design and the purposive sampling as the sampling method by distributing questionnaires to 160 people as the respondents. The results indicate that the involvement of both fashion and shopping lifestyle have a significant effects on impulsive buying. Â Keywords: Fashion Involvement, Shopping Lifestyle, Impulse Buying